Peningkatan Pelayanan Pajak Kendaraan Bermotor Pada Kantor UPT Samsat Aimas - Mainolo, Marten Aser; Bintari, Wisang Candra; ula, siti nurul nikmatul (Universitas Muhammadiyah Sorong, 2024)
ABSTRAK Motorized Vehicle Tax (PKB) is a tax on ownership and or control of motorized vehicles based on Law Number 28 of 2009. There are several problems such as services and administrative processes that take a long time resulting in queues, and a lack of public awareness and compliance in paying taxes. The purpose of this research is to find out the steps taken to bring tax services closer to the community, strategies to improve tax services through drive thru, and how to provide excellent service to the community. This research method uses a type of qualitative research. There are also data collection techniques in the form of observation, interviews, and documentation. And there are data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the motor vehicle tax service at UPT SAMSAT Aimas Sorong Regency has been running very well, the drive thru program is also very helpful in service and the community is also quite satisfied with the services provided, although it still needs to be equipped with several facilities and infrastructure and need to there are innovations made to attract people to want to come and pay taxes.